Impact of perceived organisational support on organisational citizenship behavior: special reference to hotel sector employees in sri lanka - Jayawickrama, U.W.G.Y.E.; Janadari, M.P.N. (University of Jaffna, 2022)
Purpose: Due to the perceived importance of Organisational Citizenship Behavior (OCB), numerous efforts have been made to investigate the antecedents of OCB. Emerging lines of research put forward Perceived Organisational Support (POS) as an important predictor of employee performance. Hence, the purpose of this study is to investigate the impact of POS on OCB. Methodology: The current study adopted quantitative methodology to achieve the aim of the study and deductive approach was used as the research approach. The survey strategy was used as it is associated with the deductive approach. The current study is cross-sectional, and the extent of researcher interference is minimal. The primary data was collected from three to five-star hotels in the central province, of Sri Lanka using a self-administered survey questionnaire. The sample size was computed based on the formula provided by Dillman (2000) and stratified random sampling technique was used as the sampling technique. Structural Equation Modeling (SEM) was used as the main research statistical-analysis tool. According to the reliability test results, Cronbach's Alpha values of each construct were greater than 0.7. Hence, it was concluded that there is an internal consistency of indicators used to measure the constructs. This study hypothesized that POS would impact OCB. The results demonstrated a positive and significant path from POS and OCB (â = 0.34, p < 0.001). Thus, the hypothesis was supported, and the study results revealed that POS positively impacts OCB. Findings: Hence, the findings of this study are consistent with the findings of previous research and the rationale of the organizational support theory. The current study makes an important contribution to the literature in terms of providing a more fine grained understanding of OCB and POS. This study has theoretically been able to contribute to the body of knowledge by conducting its investigation in the hotel sector in a developing country like Sri Lanka. The findings of this study provide several important implications for managers. The study found that POS as an antecedent of OCB, hence organizations in the hotel sector should motivate their customer contact employees to feel more obligated towards the organization by offering fair compensation, showing respect and recognition, support to learn new skills, providing up-to-date training and career support, and giving a realistic job and career preview. When an employee's perception of the way the organisation appreciates his or her contribution, values his or her contribution and cares about his or her well-being increases, it fosters employee performance. Implications: Despite the contributions and implications, studying only one antecedent of OCB, the cross-sectional nature of data, and quantitative methodology are the limitations of this study. Future studies may accommodate a qualitative research approach, and a longitudinal time frame and may identify other possible antecedents of OCB.
Keywords: Hotel sector; Organisational citizenship behavior; Perceived organisational support